Effect of the root canal final rinse protocols on the debris and smear layer removal and on the push-out strength of an epoxy-based sealer - Aranda-Garcia, Arturo Javier [UNESP]; Kuga, Milton Carlos [UNESP]; Vitorino, Keli Regina [UNESP]; Chávez-Andrade, Gisselle Moraima [UNESP]; Hungaro Duarte, Marco Antonio; Bonetti-Filho, Idomeo [UNESP]; Faria, Gisele [UNESP]; Reis Só, Marcus Vinicius (Wiley, 2013)
The aim of the present study was to evaluate the efficacy of QMiX, SmearClear, and 17% EDTA for the debris and smear layer removal from the root canal and its effects on the push-out bond strength of an epoxy-based sealer by scanning electron microscopy (SEM). Forty extracted human canines (n=10) were assigned to the following final rinse protocols: G1-distilled water (control), G2-17% EDTA, G3-SmearClear, and G4-QMiX. The specimens were submitted to a SEM analysis to evaluate the presence of debris and smear layer, respectively, in the apical or cervical segments. In sequence, forty extracted human maxillary canines with the root canals instrumented were divided into four groups (n=10) similar to the SEM analysis study. After the filling with AH Plus, the roots were transversally sectioned to obtain dentinal slices. The specimens were submitted to a push-out bond strength test using an electromechanical testing machine. The statistical analysis for the SEM and push-out bond strength studies were performed using the Kruskal-Wallis and Dunn tests (α=5%). There was no difference among the G2, G3, and G4 efficacy in removing the debris and smear layer (P>0.05). The efficacy of these groups was superior to the control group. The push-out bond strength values of G2, G3, and G4 were superior to the control group. The ability to remove the debris and smear layer by SmearClear and QMiX was as effective as the 17% EDTA. The final rinse with these solutions promoted similar push-out bond strength values. © 2013 Wiley Periodicals, Inc.
Keywords: Debris; Dentine; Endodontics; Scanning electron microscopy; Smear layer; biomedical and dental materials; epoxy resin; epoxy resin based root canal sealer; epoxy resin-based root canal sealer; root canal filling material; canine tooth; debridement; dental surgery; drug effect; endodontics; human; in vitro study; methodology; scanning electron microscopy; treatment outcome; Cuspid; Debridement; Epoxy Resins; Humans; Microscopy, Electron, Scanning; Root Canal Filling Materials; Root Canal Irrigants; Root Canal Preparation; Smear Layer; Treatment Outcome